Design of a Miniaturized and Polarization-Independent Frequency-Selective Surface for Targeted EMI Shielding - Muhammad Idrees; Yejun He; Youquan Wen; Abdul Majeed (Applied Sciences)
In this article, a miniaturized frequency-selective surface (FSS)-based electromagnetic shield is investigated for EMI mitigation in the X-band. The FSS comprises a convoluted conducting loop designed over an FR-4 substrate. It operates at 10 GHz X-band frequency and offers an effective shielding of at least 33 dB. It reveals rejection bandwidths of 26% for the TE and TM wave modes at normal incidence. Moreover, it accomplishes polarization-insensitive and angularly stable spectral responses owing to its structural symmetry and compact size. In addition, an equivalent circuit model (ECM) and a finite prototype of the shield are developed to verify EM simulations. A comparison of the results indicates that the FSS offers wide angular stability and excellent shielding performance, which makes it a suitable candidate for applications requiring targeted EMI mitigation.